Traditional Malay poems : reflections of courteous disposition, gracious speech and supreme wisdom of the Malay psyche. - Musa, Hashim (Dewan Bahasa dan Pustaka, 2008)
Traditional Malay Poems: A Heritage That Reflects the Wisdom of Malay Psyche Traditional Malay poems, a form of structured language constructed in rhythm with carefully and precisely chosen words such that they can be easily recalled, represent a Malay treasure-house from time immemorial. Before they were recorded, most of Malay poems were in the oral form as in maxims, pantoums, couplets, proverbs and so on.